(untitled) (Journal of Computational Intelligence and Robotics, 2022)
Automated Underwriting Systems (AUS) powered by Artificial Intelligence (AI) have revolutionized the landscape of risk assessment and decision-making in various industries, notably finance and insurance. This paper delves into the advancements and challenges intrinsic to AUS in the contemporary AI era. Key areas of focus include regulatory compliance, bias mitigation, and model interpretability. Through an extensive review of literature and analysis of case studies, this research elucidates the evolving role of AI in underwriting, highlighting its potential to streamline processes, enhance accuracy, and improve efficiency. However, the integration of AI in underwriting also poses significant challenges, such as ensuring compliance with regulatory standards, addressing inherent biases, and achieving transparency and interpretability in complex AI models. The paper examines current methodologies, best practices, and emerging technologies aimed at mitigating these challenges. Additionally, it explores the ethical and societal implications of AI-driven underwriting systems, emphasizing the importance of fairness, accountability, and transparency. By synthesizing existing knowledge and identifying gaps in research, this paper provides insights for practitioners, policymakers, and researchers to navigate the intricate landscape of AUS in the age of AI.